Evaluation of trace elements, calcium, and magnesium levels in the plasma and erythrocytes of patients with essential hyperhidrosis - Guder, Husna; Karaca, Semsettin; Cemek, Mustafa; Kulac, Mustafa; Guder, Semih (WILEY, 2011)
Background Essential hyperhidrosis is a disease that expresses itself with excessive sweating in palmar, plantar, axillary, and craniofacial regions. The etiopathogenesis of the disease, which has particular importance because of leading to psychosocial morbidity, could have not been completely elucidated. In previous studies, it has been shown that oxidative stress might play a role in the pathogenesis. Aims Assessing the levels of trace elements such as Se, Zn, Cu, Fe, and Mg that have an important role in oxidative stress, as well as Ca and Mg that have an important role in membrane physiology, in patients with essential hyperhidrosis. Materials and methods Blood samples taken from the patient group with essential hyperhidrosis (42) and the control group (37) were separated into plasma and erythrocytes, and the levels of the bioelements were measured by use of ICP-OES device. Results Erythrocyte levels of Se, Fe, Cu, Zn, Ca, and Mg were detected significantly higher in patients with essential hyperhidrosis. Furthermore, plasma levels of Cu, Ca, and Mg were significantly lower in patients with essential hyperhidrosis. Plasma levels of Se, Fe, and Zn showed no statistical difference between two groups. Dicussion It was thought that the high levels of Cu and Fe in erythrocytes may play a role in increased intracellular oxidative stress, whereas the increase in Se and Zn levels may be secondary to increased oxidative stress. Low extracellular concentrations of Ca and Mg raise the thought that they play a role either enhancing the membrane excitability of eccrine sweat glands or influencing the autonomic nerve system. Conclusion The levels of trace elements, which were determined to be different from the control group, may play a role in the pathogenesis of essential hyperhidrosis either in direct relation with or without oxidative mechanisms.
Keywords: PALMAR HYPERHIDROSIS; HUMAN PHYSIOLOGY; PATHOLOGY; Dermatology